The indigenous woman in the therapeutic-enlightened project of Peru (1861-1889) - Cruz Guerrero, Dany Erick (2022)
The article investigates the emergence of the problem of indigenous women to the critical horizon of the scientific mentality that manages the emancipatory project of Peru as an organic response to the spiritual, scientific, intellectual, and ethical-political crisis that is the natural consequence of the collapse of the archaic colonial regime in Peru and the Andean region. Consequently, this paper discusses the historical-formative, epistemological, semantic-resignifying, constructive and attitudinal aspects that intervene in the scientific formulation of our problem. This article thus explains the critical process through which indigenous women become protagonists in critical studies and, above all, producers of discourse and, therefore, of discursive criticism. This contribution concludes that the integration of indigenous women into Peruvian citizenship continues to be a current and ongoing challenge.